2007
DOI: 10.3168/jds.2007-0058
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response to Intramammary Mycoplasma bovis Infection

Abstract: The objective of the current study was to characterize the systemic and local innate immune response of dairy cows to IMI with Mycoplasma bovis, a pathogen of growing concern to the dairy industry. Ten Holstein cows were each infused in 1 quarter with M. bovis and studied for a 10-d period. Acute phase protein synthesis, which reflects 1 parameter of the systemic response to infection, was induced within 108 h of infection, as evidenced by increased circulating concentrations of lipopolysaccharide binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 45 publications
11
67
0
Order By: Relevance
“…To obtain more insight into the effects of yeast products on blood cell composition in an experimental infection model using neonatal calves, we conducted blood cell composition analysis. A previous study reported that cattle infected with Mycoplasma bovis showed systemic responses, including leukopenia, lymphopenia, neutropenia and thrombocytopenia, during the first few days of the infection, and it has also been reported that leukopenia occurs early in bacterial infections in ruminants (Kahn and Line, 2005;Kauf et al, 2007). In this study, different tendencies for changes in blood cell composition were observed between groups after vaccine challenge.…”
Section: Discussionsupporting
confidence: 48%
“…To obtain more insight into the effects of yeast products on blood cell composition in an experimental infection model using neonatal calves, we conducted blood cell composition analysis. A previous study reported that cattle infected with Mycoplasma bovis showed systemic responses, including leukopenia, lymphopenia, neutropenia and thrombocytopenia, during the first few days of the infection, and it has also been reported that leukopenia occurs early in bacterial infections in ruminants (Kahn and Line, 2005;Kauf et al, 2007). In this study, different tendencies for changes in blood cell composition were observed between groups after vaccine challenge.…”
Section: Discussionsupporting
confidence: 48%
“…54 Given their simple nature and fastidious growth requirements, they find ecological niches within their host. In cases of intramammary infections, Mycoplasma sp do not appear to often cause a significant, if any, febrile response, 48,55,56 which may be consistent with their nature to colonize cows asymptomatically.…”
Section: Carriagementioning
confidence: 77%
“…These increases were related to increased levels in milk of a range bovine cytokines including IL-1β, IFN-γ and TNF-α. Monitoring the changes in serum LBP and SAA concentrations has also been used to characterize the innate immune response to experimental induction of mastitis with Mycoplasma bovis infection [180]. The increases in serum LBP and SAA were compared along with other markers of the innate immune response, such as cytokines, between Holstein and Jersey breeds of dairy cows.…”
Section: Acute Phase Proteins In Mastitismentioning
confidence: 99%